Exploring an autoethnographic stance with poetry in children's nursing. (November 2017) - Clancy, Marie
An autoethnographic stance has been taken in this paper as this methodology can be particularly useful when exploring complex feelings and unique lived experiences. The purpose of this paper is to use this stance to holistically explore a nursing journey writing poetry during times of personal and professional difficulty, with cathartic benefits. It is hoped this will provide an example and tool for other nurses to expand their learning, insight and understanding. Poems will be used as data in this paper, and data analysis and a reflective narrative and literature exploration described to help analyse their meaning. This may stimulate an empathetic understanding in the reader and give an in-depth insight into the challenging role of the children's nurse. Poetry will be used to explore some of the typical features of autoethnography, namely self-portrayal, context, and culture with self-reflection, and by providing poetry that encourages reader exploration. Poetry has the potential to benefit nursing, including enhanced self-awareness and coping mechanisms as well as the development of empathy to support patients, families and colleagues. The use of personal poetry with reflective narrative provides an illuminating expansion of the experiences described, which may encourage readers to explore their own emotions and reflect in new and different ways.